DISRUPSI DAN MASA DEPAN PROFESI HUKUM - Widodo Dwi Putro (Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractDisruption poses a threat on legal profession establishments such as law firms, notaries, as well as the courts. In the past, law used to be perceived as a complicated matter to laypersons and thus people dealing with the law required legal consultants in the past. However, artificial intelligence capable of resolving various legal issues has now become readily available making it unnecessary for people to consult with law firms. The main question is, why is artificial intelligence capable of replacing the human legal profession? In an effort to answer the said question, the research method looks at previous research predicting the occurrence of disruption in the area of law. The researcher also considers the most recent developments in the “competition” between the human legal profession and artificial intelligence. Any technology is bound to be replaced by an even more sophisticated technology, hence the legal profession applying a mechanical legal process is inevitably going to be replaced with speedier and more accurate artificial intelligence. IntisariDisrupsi mengancam kemapanan profesi hukum seperti kantor-kantor advokat, notaris, dan juga pengadilan. Jika sebelumnya, hukum terasa rumit bagi banyak orang awam sehingga memerlukan konsultan hukum bagi yang berurusan dengan hukum, kini telah tersedia artificial intelligence yang mampu memecahkan berbagai persoalan hukum sehingga orang tidak perlu konsultasi ke kantor hukum. Pertanyaan mendasar, mengapa artificial inttelligence dapat menggantikan profesi hukum manusia? Untuk menjawab pertanyaan itu, Penulis menelusuri penelitian-penelitian sebelumnya yang memprediksi munculnya disrupsi di bidang hukum. Penulis juga melihat perkembangan terbaru “kompetisi” antara profesi hukum manusia dan artificial intelligence. Teknologi yang lebih canggih akan menggantikan sesuatu yang bersifat teknologi pula, maka profesi hukum yang cara berhukumnya mekanis akan digantikan oleh artificial intelligence yang lebih cepat dan akurat.